Frequency-doubled chirped-pulse dual-comb generation in the near-UV: combined vs separated beam investigations of Rb atoms and NO2 near 420 nm - Jasper R. Stroud; David F. Plusquellic (Scientific Reports)
Abstract We describe an electro-optic dual-comb system that operates in the near-infrared (near-IR) region to generate optical frequency combs in the near-UV by sum frequency generation in two configurations. The near-IR frequency combs are generated using chirped pulses that down convert the optical information into the radio frequency (RF) domain by a difference in the chirp bandwidths. Near-UV combs at twice the near-IR bandwidth are obtained by sum frequency generation in a nonlinear crystal and detected by a hybrid photon counting detection system. We compare the results of studies of Rb near 420 nm using two optical arrangements where the near-IR combs are mixed in the crystal as combined or as separated beams. While the latter method enables phase retrievals, the combined beam method is superior for phase stability, power throughput for detection, ease of alignment and detection sensitivity. High order interleaving enables near-UV bandwidths near 4 cm−1 for faint photonic sensing and spectroscopic applications. We demonstrate its utility as a high-resolution instrument for column detection of the toxic pollutant, NO2. The harmonic generation method is easily extendable across much of the titanium sapphire tuning range for detection of other trace gases.